1999
DOI: 10.1097/00001199-199906000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Rehabilitation on Outcomes for Persons with Traumatic Brain Injury: A Systematic Review

Abstract: We evaluated evidence for the effectiveness of cognitive rehabilitation methods to improve outcomes for persons with traumatic brain injury (TBI). A search of MEDLINE, HealthSTAR, CINAHL, PsycINFO, and the Cochrane Library produced 600 potential references. Thirty-two studies met predetermined inclusion criteria and were abstracted; data from 24 were placed into evidence tables. Two randomized controlled trials and one observational study provided evidence that specific forms of cognitive rehabilitation reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
2
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(103 citation statements)
references
References 32 publications
1
98
2
2
Order By: Relevance
“…However, as Evans 10 asserted, this view is 'largely based on the absence of evidence rather than evidence of absence of an effect of restitution oriented therapies' (p. 520). While there has been substantial growth in the number of memory rehabilitation studies, 11 systematic reviews of the effectiveness of memory rehabilitation following stroke, 12 multiple sclerosis 13 and traumatic brain injury 14 have concluded that there is insufficient evidence to support or refute the use of such rehabilitation strategies. These reviews have pointed to the poor quality and quantity of randomized trials in this area, and the diverse manner in which outcomes are assessed, leading to difficulties in converging data into a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…However, as Evans 10 asserted, this view is 'largely based on the absence of evidence rather than evidence of absence of an effect of restitution oriented therapies' (p. 520). While there has been substantial growth in the number of memory rehabilitation studies, 11 systematic reviews of the effectiveness of memory rehabilitation following stroke, 12 multiple sclerosis 13 and traumatic brain injury 14 have concluded that there is insufficient evidence to support or refute the use of such rehabilitation strategies. These reviews have pointed to the poor quality and quantity of randomized trials in this area, and the diverse manner in which outcomes are assessed, leading to difficulties in converging data into a meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They cautioned that long term benefit and clinical relevance were not well established. 11 In this study we have documented the time course and magnitude of cognitive recovery during the first six months and first one year and functional outcome after one year of TBI in a group of 70 patients. There were twelve drop outs, therefore 58 patients with moderate (n = 27) and severe (n = 31) TBI, were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Esta perspectiva é interessante, pois pode ser aplicada nos diferentes ambientes naturais das crianças e adolescentes, portanto, gerando resultados não apenas nas sessões individuais de consultório, mas facilitando sua incorporação aos hábitos rotineiros dos clientes. Carney et al (1999) realizaram uma extensa revisão bibliográfica buscando determinar quais as práticas mais eficazes em reabilitação cognitiva para pessoas com traumatismo crânio encefálico. No entanto, diante do número reduzido das amostras, das definições diferentes utilizadas pelos estudos e pela variedade dos instrumentos utilizados para avaliar as funções antes e depois das intervenções os resultados foram inconclusivos.…”
Section: Implicações Para Reabilitaçãounclassified